The Buddha in the attic - Otsuka, Julie, 1962- (Alfred A. Knopf, 2011)
Presents the stories of six Japanese mail-order brides whose new lives in early twentieth-century San Francisco are marked by backbreaking migrant work, cultural struggles, children who reject their heritage, and the prospect of wartime internment.